Development of Supervision Model based Experiential Learning for the Implementation of Patient Safety Goals at Teaching Hospital in Surabaya - Ita Maulidiawati; Nursalam Nursalam; Hanik Endang Nihayati (Universitas Airlangga, 2017)
Introduction: Patient safety is one of the demand of people who need health services. The hospital is required to fulfill the patient's safety goals. Nurses as health care providers have a risk of making mistakes and it can result in harm to the patient. The purpose of this research was to develop model of supervision based on experiential learning in the implementation of patient safety goals.Method: This research used explanatory survey. The samples were some of nurses who assigned to the ward of UNAIR hospital. The samples were selected by using stratified random sampling technique with total of 100 respondents. The variables in this research are supervision based on experiential learning and the implementation of patient safety goals. The data collection used questionnaires. The data were analyzed by using Partial Least Square (PLS).Result: The results of this study indicate that organizational characteristics and individual characteristics influence supervision based on experiential learning. Characteristics of the organization contruct by two indicators namely rewards and leadership systems. For individual characteristics, there are also two indicators that contribute on it, they are the ability and motivation. Supervision based on experiential learning affects the implementation of patient safety goals.Discussion: Supervision based on experiential learning uses four stages: concrete experience, reflective observation, abstract conceptualization and active experimentation. Supervision affects the implementation of patient safety goals by nurses in the hospital.